MATHEMATICAL EDUCATION AND THE LEARNING ASSESSMENT PROCESS IN THE EARLY YEARS OF ELEMENTARY SCHOOL: A CASE STUDY - de Souza Holanda, Magno; Britez de Matínez, Petrona (Journal of Interdisciplinary Debates, 2024)
This study analyzed the influence of parental and/or guardian involvement on the academic performance of 3rd-grade students at the Municipal School Santa Luzia in Cajazeiras, Macaíba. The specific objectives included understanding parents’ and/or guardians’ perceptions of their role in the educational process, exploring their participation in students’ learning, identifying factors that affected their effective participation, and proposing strategies to encourage greater involvement of these responsible parties in the school. A qualitative case study methodology was adopted, utilizing semi-structured interviews, analysis of official documents, and a literature review. The sample consisted of 24 3rd-grade students, 2 teachers, 2 administrators, and 10 parents and/or guardians. The results revealed a significant relationship between parental support and students’ academic performance. Students who received more support or supervision from their parents or guardians performed better academically. The study emphasizes the importance of active parental and/or guardian involvement in students’ school life, not only in terms of financial and material support but also in interaction with teachers and other members of the school community. A notable aspect of the research was the formative/summative assessment conducted with parents present in the classroom. The results of this assessment, not disclosed to the students and their families, were quite revealing: when parents were present, students’ correct responses ranged from 95% to 100%, while in the absence of parents, correct responses ranged from 20% to 50%. This result highlights the significant influence that parental participation can have on students’ academic success.